Hydrodynamics of flow through living shoreline structure - Tanhaseng Kanyarat; Kositgittiwong Duangrudee; Ekkawatpanit Chaiwat; Kompor Wongnarin; Petpongpan Chanchai (BIO Web of Conferences)
Globally, the deployment of artificial seadomes has garnered increasing attention for enhancing recreational activities and providing coastal protection. The strategic placement of seadomes on the seafloor alters local hydrodynamic patterns, which play a crucial role in mitigating coastal erosion. A comprehensive understanding of these flow dynamics is essential for optimizing the design and configuration of artificial seadomes. This study presents a numerical investigation into the hydrodynamics of artificial seadomes, focusing on performance optimization by varying key parameters such as water depth (h), incident wave height (Hi), and wavelength (L). A series of 40 controlled numerical tests was conducted with seadomes arranged in five shore-parallel rows near the shoreline. The analysis reveals that a relative structure height (D/h) exceeding 1.0, coupled with a relative wavelength (L/Be) between 0.5 and 1.0, leads to wave amplitude reductions of over 90%. Larger seadomes, with widths ranging from 45 to 60 cm, achieved wave reduction rates of up to 98%. The study also explored a zig-zag formation using 3D computational fluid dynamics (CFD) with the RNG k-ε turbulence model, offering detailed insights into the flow behavior around the structures. Furthermore, a nomogram was developed as a practical tool to optimize seadome placement for enhanced wave attenuation and coastal defense. These results provide valuable guidance for future applications of artificial seadomes in real-world coastal protection efforts.